UPAYA MENINGKATKAN MINAT BACA SISWA KELAS VII MELALUI KEGIATAN GERAKAN LITERASI DI SMP TARBIYATUl MUHIBBIN - Hasanah, Uswatun; Nurul Laili, Ulya; Syarifudin, Amir (Biro 3 Kemahasiswaan dan Kerjasama Universitas Abduracman Saleh Situbondo, 2025)
The purpose of this writing is to determine the factors that influence reading interest and interest in class VII students of Tarbiyatul Muhibbin Middle School for the 2023/2024 academic year. This type of research is qualitative research with a descriptive approach. VII SMP students are the subjects. The influencing factors are internal and external factors. Internal factors include intelligence, interest and attention, motivation, perseverance, attitude, reading habits, as well as physical fitness and health. Students will not be interested in reading if they do not have the desire, health, physical fitness, intelligence and motivation. Bad libraries, outdated reading materials, some even unused, little encouragement from teachers, no encouragement from parents, parents who do not give encouragement due to lack of funds, no parental attention to children's reading. Most parents focus more on learning outcomes, reading habits that students have not acquired since childhood. The influence of the reading environment and playmates indirectly influences students' interest in reading. The uncontrolled influence of technology. For example, the influence of misuse of smartphones or gadgets, the influence of television programs on students who forget their student responsibilities